STRATEGI KOMUNIKASI PEMASARAN PROGRAM STARONE NGORBIT DI SOLO: Studi Deskriptif Kualitatif Tentang Strategi Komunikasi Pemasaran Program STARONE Ngorbit di Solo Periode 23 November 2007-2010 - Lista, Novie Trisna (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2013)
STARONE is CDMA cellular communication card released by PT. Indosat Tbk, for Central Java and Yogyakarta. The operational of STARONE is hold by PT. STARONE Mitra Telekomunikasi. To attract customers and remind the society about the existence of STARONE which has been delayed, it is launched STARONE Ngorbit Program, Ngobrol Irit with STARONE on 23 November 2007. The study aims to know the strategy of marketing communication implemented by PT. STARONE Mitra Telekomunikasi for STARONE Ngorbit Program in Solo viewed from promotion mix consisting of advertising, sales promotion, public relations, personal selling, and direct selling applied using concept of Integrated Marketing Communication (IMC). Promotion mix is conducted integrated to achieve market continuously and widely used resulting consistent message and maximizing marketing communication objective that is greater sales. The method used is descriptive qualitative. The data are collected by observation, interview, document and purposive sampling. The data are analyzed through data reduction, display, conclusion and verification. The data validity in this research uses resource triangulation. Based on the result of the study, the writer concludes that the activity of marketing communication of PT. STARONE Mitra Telekomunikasi Solo for STARONE Ngorbit program is more enforced on sales promotion, personal selling, public relation and branding INDOSAT. The advertising activity is less enforced because it has been handled by Regional and Head Office Marketing, because the target of the activity is in national scale and gives national information